Crisis and Transformations in the Bulgarian National Consciousness - Hristov, Ivailo (Research Papers, 2014)
The study treats crisis, changes and transformations of the Bulgarian national consciousness, inspected through the prism of the essential stages of the political systems’ development in Bulgaria. The accent in the research is focused on the critical analysis of the evolution and exhausting of the patriotism, one of the oldest and significant achievement of the human civilization. The essential elements of the treated research problem are following: the progressive exhaustion of national energy; the permanent antagonism at each level: political, social, ethnic, economical; the transformation of the lack of a national identity on a tacit state policy; manipulation at the spiritual sphere. The study’s conception is based on two approaches – the political scientific and the cultural-historical, and the basic models are: the causal-consecutive and the comparative analysis.